Comparative study of the effects of VBT training with different velocity loss thresholds on lower limb explosive force of adolescent sprinters - Wang, Jingmiao; Zeng, Zhuo; Lu, Quanhong; Yuan, Song; Chai, Yunmei (Frontiers in Physiology, 2026)
ObjectivesThis study aimed to investigate the effects of velocity-based training (VBT) on lower-limb explosive performance in adolescent sprinters and to compare the training adaptations induced by different velocity loss thresholds (VLT).MethodsForty-five male adolescent sprinters were randomly assigned to three experimental groups that trained with VLT of 10% (G1), 20% (G2), and 30% (G3), respectively. All participants completed a 6-week VBT squat program performed twice per week at an intensity of 80% 1RM, with a fixed total volume of 20 repetitions per session. The session rating of perceived exertion (sRPE) was used to monitor subjective fatigue. Pre- and post-intervention tests included 30 m sprint performance, squat 1RM, countermovement jump (CMJ) height and relative peak power, and drop jump (DJ) reactive strength index (RSI). Data were analyzed using one-way ANOVA and paired-sample t-tests.ResultsAfter 6 weeks of training, all groups showed significant improvements in squat 1RM, 30 m sprint performance, CMJ height, CMJ relative peak power, and DJ RSI (p < 0.05). Between-group comparisons revealed no significant differences in 1RM improvement (p > 0.05), whereas the 10% VLT group demonstrated significantly greater enhancements in CMJ height, CMJ relative peak power, 30 m sprint performance, and RSI compared with the 30% VLT group (p < 0.05). The overall trend in performance gains was consistent: 10% VLT > 20% VLT> 30% VLT. Monitoring data showed that sRPE values increased significantly with higher VLT (p < 0.001), indicating that lower VLT settings effectively reduced fatigue accumulation.ConclusionVBT is an effective method for improving lower-limb explosive performance in adolescent sprinters. Under fixed training volume conditions, applying a lower VLT (e.g.,10%) produces superior training outcomes, likely due to reduced fatigue, maintenance of higher movement velocity and power output, and enhanced neuromuscular adaptations. Coaches are therefore advised to prioritize lower VLT when designing VBT programs aimed at developing explosive strength in youth sprinters.